Pregnancy Outcomes in Women with Incidentally Detected Unicornuate Uteri - Matthews, Kathy C.; Chasen, Stephen T. (American Journal of Perinatology, 2020)
Objective To estimate the incidence of adverse pregnancy outcomes in women with incidentally detected unicornuate uteri.Study Design This is a descriptive study. Database review identified patients with unicornuate uteri and singleton pregnancies at ≥12 weeks' gestation. Patients were excluded if the diagnosis of unicornuate uterus was made after a midtrimester loss or preterm delivery. Records were reviewed to obtain clinical outcomes. Chi-square test, Fisher's exact test, and Mann–Whitney U-test were used for statistical analysis.Results Forty patients with 67 pregnancies were included. Most diagnoses were made during infertility work-up (76.2%). There was one midtrimester loss (1.5%). In the remaining 66 pregnancies, median gestational age at delivery was 38 weeks. There were 20 (30.3%) preterm births, 9 (13.6%) spontaneous preterm births, and 11 (16.7%) indicated preterm births. Women with indicated preterm births were more likely to have placental abnormalities. Of the available placental pathology, 45.2% had histological lesions of malperfusion. Cesarean delivery was performed in 77.3% of cases.Conclusion Most women with incidentally detected unicornuate uteri gave birth at term. More than half the preterm births were indicated, with relatively high rates of placental abnormalities. In patients without a poor obstetrical history, rates of midtrimester loss and spontaneous preterm birth were lower than previously described.
Keywords: congenital uterine anomaly; incidental; lesions of malperfusion; Mullerian duct anomaly; placental abnormality; pregnancy outcomes; unicornuate uterus